Pembinaan Seni dan Pelayanan Serta Pengenalan Teknologi Informasi Kepada Anak SD dan SMP di Jemaat GKE Batang Pambelum Palangka Raya - Elvira, Elvira; Simanjuntak, Nova Lady; Ebariani, Ebariani; Pahan, Berth Penny; Egi, Al; Andari, Putri; Lawalata, Dolfi Geflesia; Nazaret, Tryoanda (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2025)
The Religious Performing Arts Study Program carries out community service with the theme of Arts Development and Service as well as Introduction to Information Technology to children at the GKE Batang Pambelum Palangka Raya Congregation. Community service aims to increase knowledge and skills in the arts for church musicians, song guides, elders and deacons, as well as introducing dramatic arts to children, teenagers and youth, as well as providing a constructive introduction to information technology to elementary and middle school aged children. The target of this activity is the congregation at the GKE Batang Pambelum Palangka Raya congregation. This Arts and Service Development uses a Participatory Action Research (PAR) approach which prioritizes the cycle of participation, action, research in the nature of service participation within the community or congregation. There are three stages in this activity, namely preparation, implementation and evaluation. The preparation stage involves a preliminary survey to see the state of the art and services in the field. At the implementation stage, artistic and service development is carried out. Then, the activity evaluation stage is carried out by collecting and summarizing data from each stage. The resulting change was an increase in the competence of preaching and liturgy. The congregation's singing competence is improving in terms of understanding and practice. For children and teenagers, the motivation to take part in drama arts training is very good, because it has never been done before. Information technology knowledge is increasingly developing to assist services and activities in carrying out school assignments.